Septal Thickness Does Not Impact Outcome After Hypertrophic Obstructive Cardiomyopathy Surgery (Septal Myectomy and Subvalvular Mitral Apparatus Remodeling): A 15-Years of Experience - Raffa, Giuseppe M.; Franca, Eluisa La; Lachina, Carlo; Palmeri, Andrea; Kowalewski, Mariusz; Lebowitz, Steven; Ricasoli, Alessandro; Greco, Matteo; Sciacca, Sergio; Turrisi, Marco; Morsolini, Marco; Stringi, Vincenzo; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: The aim of this study was to assess the impact of septal thickness on long-term outcomes of surgical treatment for hypertrophic obstructive cardiomyopathy (HOCM) and correction of mitral subvalvular anomalies. Methods: Sixty-six consecutive patients (58±12 years, 56% female) undergoing extended septal myectomy and subvalvular mitral apparatus remodelling from 2007 to 2021 were retrospectively reviewed. Patients were divided into 2 groups according to septal thickness: moderate (<18 mm, 29 patients (44%)) and severe (≥18 mm, 37 patients (56%)). End points included survival, symptom improvement, reduction of left ventricle outflow tract (LVOT) gradient, resolution of mitral regurgitation (MR), and reoperation. Results: The mean interventricular septal thickness was 19±3 mm, 15.8±0.8 mm in patients with moderate and 21.4±3.2 mm in those with severe hypertrophy. Preoperative data, intraoperative variables, postoperative complication rates, pre-discharge echocardiographic and clinical parameters did not differ between the two study groups (except for procedures involving the posterior mitral leaflet (p=0.033) and septal thickness after myectomy (p=0.0001)). Subvalvular apparatus remodelling (secondary chordae of mitral valve resection and papillary muscle and muscularis trabeculae procedures including resection, splitting, and elongation) was invariably added to septal myectomy (100%). Four (6%) procedures involved the posterior mitral leaflets. Mitral valve replacement was carried out in two patients (3%, p=0.4). Reoperation for persistent MR was necessary in one patient (1%, p=0.4). Neither iatrogenic ventricular septal defect nor in-hospital mortality occurred. During follow-up (mean 4.8±3.8 years), two deaths occurred. NYHA class was reduced from 2.9±0.7 to 1.6±0.6 (p<.0001), the LVOT gradient from 89.7±34.5 to 16.3±8.8 mmHg (p<0.0001), mitral valve regurgitation grade from 2.5±1 to 1.2±0.5 (p<0.0001), and septal thickness from 18.9±3.7 to 13.9±2.7 mm (p<0.0001). Conclusions: Regardless of septal thickness, subvalvular apparatus remodeling with concomitant septal myectomy can provide satisfactory long-term outcomes in terms of symptom improvement, LVOT obstruction relief, and MR resolution (without mitral valve replacement in most cases) in patients with HOCM.